Mitos Gebang Sewu - Thohir, Mudjahirin (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
This study examines the socio-cultural of the Gebangsewu hamlet community and their physical environment, based on an ethnographic qualitative approach. The results showed: First, the physical environment is classified as poor because it is not touched by government funded development projects. Second, after being tracked down, this condition is related with the power politics of the government of the new (orde baru) order era at that time. The people of Gebang Sewu, are partisans of the opposition party (PPP), while the government apparatus must be completely loyal to the Golkar party. Second, the social separation happened, is confirmed through negative myths about the government apparatus. It is used as "revenge" to ignore development. The findings give a message, first, that there is a social segregation between pro-government and opposition political parties. Third, uneven development due to discriminatory politics that was deliberately scripted by the New Order government.